Performance analysis of the toroidal field ITER production conductors. (18th April 2017) - Breschi, M; Macioce, D; Devred, A
Abstract: The production of the superconducting cables for the toroidal field (TF) magnets of the ITER machine has recently been completed at the manufacturing companies selected during the previous qualification phase. The quality assurance/quality control programs that have been implemented to ensure production uniformity across numerous suppliers include performance tests of several conductor samples from selected unit lengths. The short full-size samples (4 m long) were subjected to DC and AC tests in the SULTAN facility at CRPP in Villigen, Switzerland. In a previous work the results of the tests of the conductor performance qualification samples were reported. This work reports the analyses of the results of the tests of the production conductor samples. The results reported here concern the values of current sharing temperature, critical current, effective strain and n -value from the DC tests and the energy dissipated per cycle from the AC loss tests. A detailed comparison is also presented between the performance of the conductors and that of their constituting strands.